Initial Quantification of Low Frequency Masking Potential of a seismic survey - McCauley, Robert; Gedamke, Jason (International Whaling Commission, 2010)
A distant seismic survey was recorded on 3 autonomous long term acoustic recorders deployed between Tasmania and the Antarctic continent. These instruments were located approximately 450, 1500, and 2800km from the survey site. Recordings were analyzed for the presence of airgun signals with sound files from a five day period separated into 'seismic' vs. 'non-seismic' files for acoustic analysis. Sound levels across a 20-50Hz bandwidth were calculated for 1s samples and compared between the seismic and non-seismic datasets to assess the percentage of time that sound levels increased due to the presence of airgun signals. During seismic operations, a distinct shift in the distribution of sound pressure levels in the 1s samples occurred suggesting even during 'quiet' periods between shots, sound levels remained slightly elevated. Here we present results quantifying the received levels of seismic airgun shots, and the percentages of time that sound levels are elevated at varying distances from a seismic survey.